Illegal Fishing in Kosovo: An Examination of National Legislation and the Standards of European Union Law in This Field - Bytyqi, Vilard (PRAWO i WIĘŹ, 2025)
The issue of illegal fishing is being addressed through legal measures in the administrative and criminal fields. Kosovo has addressed this issue with special laws. The Law on Fisheries and Aquaculture has been implemented to regulate administrative violations, while the Criminal Code outlines the penalties for criminal offenses in this sector. This paper aims to address the aspect of regulating illegal fishing both from the perspective of administrative law and from the perspective of criminal law. The paper will address the issue of the elements that constitute the criminal offense of illegal fishing, analyzing all the objective and subjective elements that constitute this criminal offense. The analysis will also cover the administrative and criminal sanctions imposed for violations in the field of illegal fishing. The analysis will also address the issue of double regulation, as expressed in the Kosovo legal framework, where the same situation is addressed as both an administrative violation and a criminal offense without clear limits or criteria for division. The analysis will conclude with an examination of the standards promoted by the European Union in the field of illegal fishing, as well as comparative examples of some European Union countries that have adopted a more lenient approach to preventing and combating illegal fishing. These countries view administrative law as the most straightforward and least burdensome solution to address this issue.